Knowledge and attitude of general population towards climate change and its impact on health in Ismailia Governorate, Egypt - Sarah M. Hussein; Bassma A. Ibrahim (SpringerOpen, 2024)
Abstract Background Recently, climate change (CC) has garnered significant global attention. It has emerged as one of the most pressing environmental issues, resulting in a multitude of adverse impacts on human well-being and health. This study aims to assess the knowledge and attitude of the general population in Ismailia Governorate, Egypt, about CC and its impact on health, identify factors affecting the general population's knowledge about CC, and highlight methods to solve this problem. Methods A cross-sectional study was carried out on the general population in Ismailia governorate, Egypt. A snowball sample of participants (n = 150) was enrolled in the study by distributing an online Google form containing a structured self-administered questionnaire. Results The participants had an average knowledge score of 27.42 ± 14.42, with 60% considered knowledgeable. About 54% knew the main cause of CC. Around 75% were aware of the environmental impacts of CC, and 69.3% knew about the effects on human health. Based on the questionnaire's results, 76.7% of respondents believed that increasing afforestation helps in the mitigation of CC and 77.3% believed that governments bear the responsibility for CC. Approximately 85% regarded increasing green spaces as an effective method to reduce CC on the country level. On an individual level, usage of energy-saving products was the most-favored option chosen by participants to help in reducing CC (82%). Gender, education level, and place of residence were significant factors affecting knowledge about CC. Conclusions Over 50% of the participants were knowledgeable about CC and the role of human activities in CC. Therefore, public awareness campaigns utilizing prominent media such as television and social media should be launched to improve CC literacy. These campaigns should be more directed at males, and people with lower levels of education and who live in rural areas in Ismailia Governorate, Egypt.